Praktikum Pengukuran Menggunakan Model Discovery Learning Untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik di SMK Muhammadiyah Kutowinangun - Tariska Widiastuti; Umi Pratiwi; Siska Desy Fatmaryanti; Yusro Al Hakim (Universitas PGRI Semarang, 2022)
This study aims to improve the scientific literacy of students in the measurement practicum. The research method used is the experimental design method of pre experimental design (nondesigns) using One-Group Pretest-Posttest Design to determine scientific literacy ability. The measured scientific literacy ability consists of 3 aspects, namely the concept of science, the process of science, the situation and the realm of application. The research activity was attended by 28 students of class X TKRO-F. The learning model used is discovery learning. Discovery learning is divided into six stages, namely stimulation or giving stimulation, problem identification, data collection, data processing, verification, and generalization or conclusions. The research instrument uses pretest questions which are carried out at the beginning of the practicum activity and the posttest is carried out after the practicum. The results of this study are able to measure success in carrying out physics practicum. Based on the increase in the value of the scientific literacy test results for the Measurement material, it was significantly 10.4 points, while the percentage of students who completed it increased by 2.52% and there was a decrease in the number of students who did not complete it by 2.52%. The increase in scientific literacy skills calculated using the N-gain is 0.32 in the medium category. Based on the research, it can be concluded that the discovery learning model can be used to improve students' scientific literacy skills.Keywords: discovery learning, scientific literacy, pre test, post test, practicum